Identification of novel immune correlates of protection against acute bovine babesiosis by superinfecting cattle with in vitro culture attenuated and virulent Babesia bovis strains - Bastos, Reginaldo G.; Laughery, Jacob M.; Ozubek, Sezayi; Alzan, Heba F.; Taus, Naomi S.; Ueti, Massaro W.; Suarez, Carlos E. (Frontiers in Immunology, 2022)
Apicomplexan tickborne parasites of the genus Babesia are the causative agent of babesiosis, a disease that negatively impacts public and animal health around the world. Absence of correlates of protection represents one major impediment for the development of effective and sustainable vaccines against babesiosis. Herein we superinfected cattle with attenuated and virulent strains of Babesia bovis to investigate immune correlates of protection against acute bovine babesiosis. Three 6-month-old Holstein calves were infected intravenously (IV) with the in vitro culture attenuated Att-S74-T3Bo B. bovis strain (106 infected bovine red blood cells (iRBC)/calf) while three age-matched Holstein calves were inoculated IV with normal RBC as controls (106 RBC/calf). All Att-S74-T3Bo-infected calves showed a significant increase in temperature early after inoculation but recovered without treatment. Att-S74-T3Bo-infected calves also developed: (a) monocytosis, neutropenia, and CD4+ lymphopenia in peripheral blood on days 3 to 7 post-inoculation; (b) significant levels of TNFα, CXCL10, IFNγ, IL-4, and IL-10 in sera at day 6 after infection; and (c) IgM and IgG against B. bovis antigens, starting at days 10 and 30 post-inoculation, respectively. At 46 days post-Att-S74-T3Bo inoculation, all experimental calves were infected IV with the homologues virulent B. bovis strain Vir-S74-T3Bo (107 iRBC/calf). All Att-S74-T3Bo-infected calves survived superinfection with Vir-S74-T3Bo without displaying signs of acute babesiosis. In contrast, control animals showed signs of acute disease, starting at day 10 post-Vir-S74-T3Bo infection, and two of them were humanely euthanized at days 13 and 14 after inoculation due to the severity of the disease. Also, control calves showed higher (P<0.05) parasite load in peripheral blood than animals previously exposed to Att-S74-T3Bo. No significant alterations in the profile of leukocytes and cytokines were observed in Att-S74-T3Bo-inoculated after Vir-S74-T3Bo infection. In conclusion, data demonstrate novel alterations in the profile of blood immune cells and cytokine expression in peripheral blood that are associated with protection against acute babesiosis. These identified immune correlates of protection may be useful for designing effective and sustainable vaccines against human and animal babesiosis.